Bio‐effect of nanoparticles in the cardiovascular system. Issue 11 (30th June 2016) - Yu, Xiaohong; Hong, Fashui; Zhang, Yu‐Qing
Abstract: Nanoparticles (NPs; < 100 nm) are increasingly being applied in various fields due to their unique physicochemical properties. The increase in human exposure to NPs has raised concerns regarding their health and safety profiles. The potential correlation between NP exposure and several cardiovascular (CV) events has been demonstrated. The aim of this review is to provide a comprehensive evaluation of the current knowledge regarding the bio‐toxic impacts of titanium oxide, silver, silica, carbon black, carbon nanotube, and zinc oxide NPs exposure on the CV system in terms of in vivo and in vitro experiments, which is not fully understood presently. Moreover, the potential toxic mechanisms of NPs in the CV system that are still being questioned are elaborately discussed, and the underlying capacity of NPs used in medicine for CV events are summarized. It will be an important instrument to extrapolate relevant data for human CV risk evaluation and management. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 2881–2897, 2016.